Independent Women's Voices in 'Cut Nyak Dien': An Applied Linguistic and Contextual Analysis - Suhardi Suhardi; Rosmawaty Harahap (Journal of Aceh Studies, 2025)
Background of the problem: During the colonial period, the struggle for independence in Indonesia encompassed sacrifices, warfare, and diplomatic efforts. Despite the traditional and localized nature of early 18th-century women's resistance movements, this study scrutinizes the significant influence of individual pioneers on the wider struggle. Purpose: This research aims to elucidate the character values and fighting spirit embodied by Cut Nyak Dien, an iconic pioneer of women's resistance in Indonesia. Historically, regional fighters in the archipelago primarily resisted 18th-century colonialism to defend religion and state sovereignty. Method: Employing a historical research methodology with a library study approach, this study reveals that Cut Nyak Dien's fierce loyalty, indomitable spirit, and steadfast faith profoundly reflect the inherent kindness and courage of her people. Result: Her struggle exemplifies a relentless, unyielding resolve against colonial rule, inspiring subsequent generations of Acehnese and other Indonesian women to continue the resistance. Implication: The findings underscore Cut Nyak Dien's critical role in shaping the trajectory of women's involvement in the Indonesian independence movement, establishing a powerful legacy of resilience and leadership against colonial oppression.